Analysis of the Strengthening Program of Religious Moderation Values in Islamic Boarding School Students - Irmansyah, Irmansyah; Romlah, Romlah; Ayu, Sovia Mas (Journal of Advanced Islamic Educational Management, 2024)
This study aims to analyze the program of strengthening the values of religious moderation in students of Nashihuddin Islamic Boarding School in Bandar Lampung. Religious moderation is an important concept that emphasizes a middle and balanced attitude in carrying out religious teachings, which supports diversity and tolerance. This research uses a qualitative approach with interview, observation, and documentation methods to collect data from various sources, including leaders, administrators, and students of the boarding school. The results show that the programs to strengthen religious moderation at Nashihuddin Islamic Boarding School have succeeded in increasing interfaith tolerance, strengthening intercultural relations, and increasing the social involvement of students. In addition, these programs also have a positive impact on the image of the boarding school in the eyes of the surrounding community, as well as contributing to local social and economic development. Santri are taught to understand and respect religious diversity, which helps to reduce interfaith tensions and promote peace and tolerance. The article also identifies some challenges in the implementation of these programs, such as the need to update the education curriculum to include more materials on religious moderation, as well as the need for specialized training for staff and teachers.Recommendations include developing cooperation with other educational institutions, government agencies and civil society organizations to expand the positive impact of religious moderation values. Thus, this article concludes that strengthening the values of religious moderation in Islamic boarding schools is very important to shape the character of santri who are inclusive, tolerant, and contribute positively to society. Continuous efforts and support from various stakeholders are needed to improve the effectiveness of these programs.